Desain Architecture Technology Menggunakan Togaf Adm Pada Yayasan Cawan Dadap - Wijaya, Hermawan; Lee, Francka Sakti (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The development of information systems technology has had a significant impact, especially on the education sector, changing the learning paradigm and presenting new opportunities. As technology develops, the technology used must also be updated and adapted to the existing business processes at the Cawan Dadap Foundation. The Cawan Dadap Foundation is a foundation that operates in the education sector which currently has 5 schools, namely SMAS Bethel, SMP Bethel Kosambi, SDS Bethel Kosambi, Kindergarten Bethel Kosambi, SD Agape Kudus. The problems they are facing at the moment require a system. library application and also an inventory application system which will help their business processes, the library application system will help with purchasing, borrowing, and also checking books at each of their schools, the inventory application system is useful for knowing what kind of goods I need lacking or want to add more and know the stock units of their goods. So the researchers used the TOGAF ADM framework which can help in the process of building the application system that they want the Cawan Dadap Foundation to use. The results of this research produce an application system design that will be useful in creating the application system.